Calibration of ventilation/perfusion match in electrical impedance tomography: a novel method based on arterial blood pressure - Han, Tixin; Qin, Yangchun; Zhao, Zhibo; Yang, Bin; Liu, Xuechao; Li, Lei; Wei, Ziyu; Wei, Liping; Liu, Yifan; Fu, Feng (Frontiers in Physiology, 2025)
IntroductionElectrical impedance tomography (EIT) enables non-invasive, continuous, bedside evaluation of ventilation/perfusion (V/Q) match. To avoid the presence of invasive monitoring for cardiac output in relative V/Q ratio calculation, we proposed a novel calibration method based on arterial blood pressure to optimize EIT V/Q match assessments.MethodsWe involved 12 mechanically ventilated piglets in three experimental phases: baseline, pulmonary embolism, and atelectasis. After a thorough measurement of EIT signals, arterial blood pressure, cardiac output, and additional physiological parameters, EIT V/Q match was evaluated using existing area limited method (ALM), cardiac output calibrated method (COCM), and our proposed novel blood pressure calibrated method (BPCM). Finally, VD/VT and P/F ratio were calculated and correlated with V/Q match indicators derived from COCM and BPCM.ResultsArterial blood pressure waveform integration demonstrated strong correlation with cardiac output (R2 = 0.80, p < 0.001), validating its utility for cardiac output estimation and V/Q match calibration. Both COCM and BPCM provided enhanced V/Q match region segmentation compared to ALM, yielding comprehensive diagnostic information with statistically significant differences across all three states (p < 0.05). COCM demonstrates a slightly higher correlation compared to BPCM (r = −0.63 vs. −0.52) between low ventilation index (LVI) and VD/VT, while BPCM demonstrates a slightly higher correlation compared to COCM (r = 0.49 vs. 0.44) between low perfusion index (LQI) and P/F ratio.ConclusionThis study described a novel calibration method for calculating corrected EIT-based V/Q match that utilized arterial blood pressure. Our method exhibited comparable capability in distinguishing V/Q mismatch areas compared to conventional cardiac output-based calibration techniques. With clinical data to establish a linear regression model, our method will ultimately enable us to calculate calibrated EIT V/Q match without cardiac output monitoring.